The Essence Of Political Education In The Academic Environment Of The Faculty Of Teacher Training And Education Unpam (FKIP UNPAM) (Wiyatamandala, 2025)
The Essence of Political Education in the Academic Environment of the Faculty of Teacher Training and Education, UNPAM (FKIP UNPAM), Pamulang, South Tangerang-Banten. Political education is an intentional, deliberate, and systematic educational effort aimed at shaping individuals to be politically aware and capable of acting as responsible political participants, both ethically and morally, in achieving political goals. The objective of this research is to understand the essence of political education within the academic environment of the Faculty of Teacher Training and Education at UNPAM (FKIP UNPAM). The research methodology employed is qualitative descriptive analysis, utilizing survey instruments, observations, and documentation. Once the research data is collected, it will be processed using qualitative analysis techniques by reducing, organizing, and then describing the data qualitatively. The findings indicate that political education within the FKIP UNPAM academic community has been implemented effectively, both through direct and indirect political education approaches.